Kanvas Model Bisnis Usaha Mikro Kecil dan Menengah Keripik Sawi Putih “Krauk” - Zebua, Damara Dinda Nirmalasari; Kartikowati, Maresti; Sacca, Krisna Candra Arya; Mule, Friskilia Sampe; Prayogo, Wahyu Adi; Leonaldo, Leonaldo; Ristiana, Dani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Micro, Small and Medium Enterprises (MSMEs) "Krauk" white mustard chips are one of the businesses in Sumberejo Village which was only established in 2020. The aim of this research is to describe the business model run by the MSME "Krauk" white mustard chips. The method used is descriptive qualitative. The results of the research show that the MSME "Krauk" White Mustard Chips already has an operational pattern that can be mapped into nine elements of the business model canvas including: 1) customer segments, namely all groups, especially vegetarians as consumers; 2) value proposition, namely mustard chips which taste delicious and have a crunchy texture; 3) channels, namely product marketing media, including agents/resellers and digital platforms (Shopee and Instagram); 4) customer relationship, namely efforts to maintain long-term relationships with partners by providing product samples to potential agents/resellers and providing cash and non-cash payment methods; 5) revenue stream, namely the sale of white mustard chips as the main income and the sale of peanut chips and anchovy chips as additional income; 6) key resources, namely collaboration between the MSME White Mustard Chips "Krauk" and suppliers of additional/complementary ingredients; 7) key activities, namely producing white mustard chips, peanut chips and anchovy chips; 8) key partners, namely the government (Indonesia Financial Group), tourist destinations and souvenir shops that support the "Krauk" White Mustard Chips MSME business; and 9) cost structures, namely the mandatory expenditure of "Krauk" White Mustard Chips MSMEs to purchase raw materials and additional materials as well as several other items.